The Impact of Lyrical Poetry on Student Vocabulary Acquisition - Sibuea, Erni Rawati; Siregar, Parlindungan; Sembiring, Johannes (ETANIC Journal Of English Language Teaching And Applied Linguistics, 2024)
In this research is carried out in order to know about how far the effectiveness of using lyrical poem in improving students’ vocabulary at the eleventh grade of SMA Negeri 1 Angkola Barat is. And in this research the writer applies the total random research. The number of sample in this research is consist of 36 students. The method used in this study was a quantitative method. In collecting the data, the writer administered pre-test, post-test and questionnaire which consists of 25 questions of pre & post-test and 8 question of questionnaire. After administering test and questionnaire to the sample of study, then the writer documented the students’ score. Then the writer calculated it with the score  using SPSS  v.22. In analyzing the data, the writer used SPSS v.22. After analyzing the data  in SPSS v.22, it has been got that the average mean before treatment (Pre-Test) is 53.22, the average mean after treatment (Post-Test) is 89.56, the average mean before treatment (Pre-Questionnaire) is 24.92 and  the average mean after treatment (Post-Questionnaire) is 30.44. After got the average mean, the writer  used SPSS v.22 again to analyze how far the improving students’ vocabulary, it has been got that percentage improving students’ vocabulary is 68.28%. It mean that There is a significant improvement of the students’ vocabulary at the eleventh grade students’ of SMA Negeri 1 Angkola Barat. And the hypothesis of this research is accepted.